2018
DOI: 10.3892/ol.2018.8911
|View full text |Cite
|
Sign up to set email alerts
|

PO2‑based biodosimetry evaluation using an EPR technique acts as a sensitive index for chemotherapy

Abstract: The partial pressure of oxygen (PO2) in the tumor microenvironment directly affects tumor sensitivity to chemotherapy. In the present study, a lithium phthalocyanine probe was implanted into MCF-7 human breast cancer cells, followed by transplant of the cells into nude mice. The present study used an electron paramagnetic resonance (EPR) oximetry measuring technique to dynamically monitor PO2 in the tumor microenvironment prior to and following chemotherapy, and aimed to determine the precise time window in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…EPR oximetry is minimally invasive and can measure oxygen levels both in vitro and in vivo [288,289]. Studies have demonstrated the effectiveness of using this technique to monitor ischemic or hypoxic tissue oxygenation [288,[290][291][292][293]. The underlying principle of EPR oximetry is that electrons with unpaired spins absorb radiation and move from low to high energy levels when exposed to magnetic fields [288].…”
Section: Mitochondrial Bioenergetics: Glycolytic and Respiratory Capa...mentioning
confidence: 99%
“…EPR oximetry is minimally invasive and can measure oxygen levels both in vitro and in vivo [288,289]. Studies have demonstrated the effectiveness of using this technique to monitor ischemic or hypoxic tissue oxygenation [288,[290][291][292][293]. The underlying principle of EPR oximetry is that electrons with unpaired spins absorb radiation and move from low to high energy levels when exposed to magnetic fields [288].…”
Section: Mitochondrial Bioenergetics: Glycolytic and Respiratory Capa...mentioning
confidence: 99%